2022
DOI: 10.1515/reveh-2021-0170
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of medical waste management methods in different countries: a systematic review

Abstract: Medical waste status is a severe public health problem worldwide. Proper medical waste management is of paramount importance. However, there is insufficient information about medical waste management and lack of management in different countries. The aim of this research was to investigate and evaluate the present status of medical waste management in different countries. We systematically searched Embase, PubMed/MEDLINE, Scopus, PubMed Central, Google Scholar databases, as well as medRxiv using the following … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 37 publications
0
10
0
Order By: Relevance
“…In countries where medical waste is mostly incinerated, the emissions from waste disposal could be higher. 55 Across several countries, the mass of waste varied by an order of magnitude from 250 g at AECS, other Indian sites and in Eswatini, to over 4 kg in the United Kingdom. 37,38,42,44 A prospective assessment of cataract surgery waste in Malaysia found a similar mass of around 1 kg per case, and highlighted the wide range of packaging for common items, and the potential for reducing packaging, re-using items and recycling.…”
Section: Indirect Emissions From Waste Disposalmentioning
confidence: 99%
See 1 more Smart Citation
“…In countries where medical waste is mostly incinerated, the emissions from waste disposal could be higher. 55 Across several countries, the mass of waste varied by an order of magnitude from 250 g at AECS, other Indian sites and in Eswatini, to over 4 kg in the United Kingdom. 37,38,42,44 A prospective assessment of cataract surgery waste in Malaysia found a similar mass of around 1 kg per case, and highlighted the wide range of packaging for common items, and the potential for reducing packaging, re-using items and recycling.…”
Section: Indirect Emissions From Waste Disposalmentioning
confidence: 99%
“…Waste disposal was a very minor source of emissions in these cataract footprinting studies, as general medical waste to landfill does not decompose and generate greenhouse gases. In countries where medical waste is mostly incinerated, the emissions from waste disposal could be higher 55 . Across several countries, the mass of waste varied by an order of magnitude from 250 g at AECS, other Indian sites and in Eswatini, to over 4 kg in the United Kingdom 37,38,42,44 .…”
Section: Ophthalmology Footprintmentioning
confidence: 99%
“…Rational classification of medical waste is one effective method for containing the infection and preventing the spread of the epidemic from the source. However, currently only about 25% of countries classify medical waste (Fadaei, 2022). Moreover, most guidelines or available technologies are not entirely suitable for the current national situation.…”
Section: Discussionmentioning
confidence: 99%
“…However, currently only about 25% of countries classify medical waste (Fadaei, 2022). Moreover, most guidelines or available technologies are not entirely suitable for the current national situation.…”
Section: Recommendationsmentioning
confidence: 99%
“…In addition, deficiencies found in the cases of some countries referred to the stages of collection, storage, transport, and transfer of these typical wastes, as well as the organization of the elimination of their management activities. In the same research, it was found that only a quarter of the investigated countries simultaneously applied three techniques for the elimination or treatment of sanitary waste (i.e., autoclaving, incineration, or storage), with 91% usually using incineration [19].…”
Section: Introductionmentioning
confidence: 99%